Dynamic thiol disulfide homeostasis in painters as indices of oxidative stress. Issue 5 (4th May 2022) - Özakıncı, Osman Gökhan; Gündüzöz, Meside; Buyuksekerci, Murat; Karataş, Mevlüt; Balik, Ahmet Rifat; Neselioglu, Salim; Erel, Özcan
ABSTRACT: This study was designed to determine thiol-disulfide homeostasis as indices of oxidative stress in painters by using a novel and automated colorimetric measurement method. Male painters ( n = 117) were separated into three groups according to duration of work; group 1 (<5 years), group 2 (5–14 years) and group 3 (≥15 years). Hippuric acid, trichloroacetic acid (TCA), and phenol in urine was determined. Catalase activity and ischemia-modified albumin (IMA) levels were also assessed. Disulfide/Native Thiol and Disulfide/Total Thiol of group 2 and group 3 were significantly higher than those of group 1 ( p < 0.001). A positive correlation was observed between urinary phenol and disulfide/native thiol ( r = 0.214, p = 0.035), IMA ( r = 0.305, p = 0.002), disulfide ( r = 0.209, p = 0.040), and duration of work ( r = 0.341, p < 0.001). The newly developed automated colorimetric method used in our study proposes a promising, practical and daily applicable test for evaluating oxidative status of painters.